Fairy tail. 48 - Mashima, Hiro, 1977- (Kodansha Comics, 2015)
"With her curse magic, Kyoka has deprived Ezra of all her sense- except pain, which she has amplified into excruciating torture! But even in these hopeless circumstances, the Fairy Queen continues to counterattack! Meanwhile, the duels between Igneel and Acnologia and between Natsu and the Underworld King rage on, as dragon father and wizard son struggle to grab onto a sliver of hope! The twin dragons of Saber Tooth, Rogue and Sting, show up to help. Can the joint efforts of three dragon slayers force Mard Geer to get serious? The critical moment arrives in the battle between fairies and demons!"